The VoIP backlash. - Cherry, S. (IEEE spectrum)
A seven-year-old Mountain View, Calif., company, Narus Inc., has devised a way for telephone companies to detect data packets belonging to VoIP applications and block the calls. Narus's software can secure, analyze, monitor, and mediate any traffic in an IP networks. It can also diagnose, and react to, denial-of-service attacks and dangerous viruses and worms as they wiggle through a network.